2021
DOI: 10.1093/cid/ciab961
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of the Late-Onset Efavirenz Neurotoxicity Syndrome (LENS)

Abstract: Background The late-onset efavirenz neurotoxicity syndrome (LENS) presents as ataxia and/or encephalopathy with supratherapeutic efavirenz plasma concentrations (>4 µg/mL). Efavirenz is primarily metabolized by cytochrome P450 2B6 (CYP2B6), with CYP2A6 as an accessory pathway. We hypothesized that participants with LENS would predominantly be CYP2B6 slow metabolizers. The aim of our study was to determine the frequency of CYP2B6 slow metabolizers in participants with LENS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…T/T genotype is associated with higher plasma and CSF concentrations of EFV (Haas et al, 2004;Nightingale et al, 2016), as well as late onset efavirenz neurotoxicity syndrome (van Rensburg et al, 2021). Further, in silico modeling indicates that measurements of EFV in the CSF likely underrepresent the EFV penetration into the brain (Curley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T/T genotype is associated with higher plasma and CSF concentrations of EFV (Haas et al, 2004;Nightingale et al, 2016), as well as late onset efavirenz neurotoxicity syndrome (van Rensburg et al, 2021). Further, in silico modeling indicates that measurements of EFV in the CSF likely underrepresent the EFV penetration into the brain (Curley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Up until 2018, EFV was one component of the first line treatment (WHO, 2018), and is still utilized in resource limited settings. EFV is associated with neurological adverse events, such as dizziness, depression, impaired concentration, disordered sleep, and anxiety (Fumaz et al, 2002;Gutierrez et al, 2005;Romao et al, 2011;Ma et al, 2016;Checa et al, 2020;Hakkers et al, 2020;van Rensburg et al, 2021). Higher plasma concentrations of EFV and its primary metabolite, 8-hydroxyefavirenz (8-OHEFV), have been linked to poorer neurocognitive performance and mood changes (Grilo et al, 2016;Hakkers et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a study using pharmacokinetic simulations, the efavirenz concentrations in brain tissue were found to be higher compared to plasma or CSF concentrations and in a recent study of patients with late-onset efavirenz toxicity, the 8-hydroxy-efavirenz levels were even decreased. 12 , 25…”
Section: Discussionmentioning
confidence: 99%
“… 11 A recent study of 15 patients with late-onset efavirenz toxicity found that all had polymorphisms of CYP2B6 which result in slower metabolism of efavirenz. 12 Isoniazid inhibits the CYP2A6 enzyme, which is an accessory pathway to metabolise efavirenz. Although usually only a small proportion of efavirenz is metabolised via this enzyme, it becomes more important in slow metabolisers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation